Femtosecond laser written long period grating in a multimode CYTOP polymer fibre - Theodosiou, Antreas; Min, Rui; Leal, Arnaldo G.; Ioannou, Andreas; Frizera-Neto, Anselmo; José Pontes, Maria; Marques, Carlos Alberto F.; Kalli, Kyriacos (My University, 2020)
We report on the inscription of a long period grating (LPG) in a multimode cyclic transparent optical polymer (CYTOP) fibre using the plane-by-plane femtosecond laser inscription method. The LPG was inscribed in the centre of the fibre core and tailored for operation at C-band wavelength range. The CYTOP-LPG sensitivity was characterised in transmission for relative humidity and temperature. The humidity measurements performed are the first for a POF-LPG, whereas the temperature sensitivity is significantly higher than reported in other works. In addition, dynamic mechanical measurements were performed comparing the mechanical characteristics of the laser exposed sections of the polymer fibre, where the LPG was inscribed, with the unexposed regions.
Keywords: Femtosecond lasers; Fibre Bragg gratings; Long period gratings; Optical sensors; Polymer sensors